Severe Acquired Primary Hypothyroidism in Children and its Influence on Growth: A Retrospective Analysis of 43 Cases - Becker, Marianne; Blankenstein, Oliver; Lankes, Erwin; Schnabel, Dirk; Krude, Heiko (Experimental and Clinical Endocrinology & Diabetes, 2021)
Introduction Severe acquired hypothyroidism in childhood is a rare condition, mostly caused by autoimmune thyroiditis. Scarce and inconsistent data based on small patient numbers exist concerning its impact on growth in height.Methods Patient files at a single centre university hospital over 8 years were retrospectively reviewed. We identified 43 patients (mean age 10.6 years, 3.3–15.25, 59% prepubertal, 88% females) in a cohort of children older than 3 years with an initial TSH>30 mIU/l and reduced T4 or fT4; congenital and drug-induced hypothyroidism were excluded.Results All patients had signs of autoimmune thyroiditis (93% positive autoantibodies, 95% typical ultrasonography, 63% goiter). Median TSH was 100 mIU/l [0.3–4 mIU/l]), median fT4 3.55 pg/ml [8–19 pg/ml], median T4 2.85 µg/dl [5.3–11 µg/dl]. Presenting symptoms included goiter (26%), tiredness (23%), weight gain (19%), and growth retardation (19%). The diagnosis was made incidentally in 26% patients. In 75% growth was retarded (median height standard deviation score (SDS)-0.55), in 17% height SDS was<-2 at diagnosis. Midparental height SDS at diagnosis correlated significantly with T4 and fT4 (r=0.77, p=0.0012 and r=0.53, p=0.021 respectively). Catch-up growth under T4 substitution was significantly greater in prepubertal than in pubertal children (p 0.049).Conclusion This so far largest pediatric cohort with severe acquired hypothyroidism confirms a serious impact on growth which, however in most cases, showed a certain catch-up growth after adequate L-thyroxine therapy. The pubertal state seems to be important for catch-up growth. A significant number of patients were not diagnosed clinically, although affected by severe hypothyroidism.
Keywords: thyroiditis; catch-up growth; pubertal state; presenting symptoms